How to bring food systems "From Fragility to Stability" - Goldberg, Mark Leon; Elouafi, Ismahane; Harper, Andrew; Husain, Arif; Kosec, Katrina (Global Dispatches, 2024)
This Global Dispatches podcast episode is the launch of a new series called "From Fragility to Stability" in which we examine what works to improve the well-being of people in Fragile and Conflict-Affected Settings who often struggle to sustain resilient food, land, and water systems in the face of the climate crisis. The series is produced with CGIAR, a global partnership that unites international organizations engaged in research about food security, to help deepen understanding of fragility, conflict, and migration dynamics. Episodes in this series will convene experts, practitioners, policymakers, and stakeholders to foster a collaborative dialogue, share insights, and co-create actionable strategies to address the multifaceted challenges of conflict, crises, and fragility.